Optimasi Laju Alir Pengeringan Semprot Mikropartikel Asiklovir dengan Kitosan dan Natrium Tripolifosfat - Cynthia Marisca Muntu; Jessica Clarissa Selan; Sadono (Keluwih)
Abstract—The solubility and bioavailability limitations of acyclovir can be addressed through the microparticles formulation using the spray drying (SD) method. In this study, chitosan and sodium tripolyphosphate were utilized as cross-linking agents in acyclovir microparticles (MA). This study aims to investigate the influence of SD flow rates on MA formation. The SD flow rates were set at 7.5 (L1), 6.5 (L2), and 5.5 (L3) mL/min. Functional group identification confirmed cross-linking in all MA samples. Melting point and thermal energy parameters analysis revealed differences in endothermic values between chitosan and all samples. The particle diameters of MA in L1, L2, and L3 were 8.03, 8.78, and 8.57 µm, respectively. All MA samples exhibited a roughly spherical shape. The encapsulation efficiency of L1, L2, and L3 ranged from 118.25% to 122.79%. The swelling percentage after 30 minutes reached 178.67%. The lowest moisture content of MA was observed in the L2 sample at 3.27%. The highest yield recovery was obtained in the L2 sample at 47.26%. The dissolution profiles of all samples demonstrated controlled release profile. The SD flow rate influenced encapsulation efficiency, swelling, moisture content, drug release, and yield recovery. The best characteristics of MA were achieved at a flow rate of 6.5 mL/min.